Comparative Physiological Parameter Changes between Late Blight Infected and Herbal Foliar Spray Treated Tomato Plants (Solanum lycopersicum L.) - , P. Janani, M. Kabilan, L. Sowmiya, V. Raja, K. Poonkodi, P. Arun, E. Nagalakshmi (Archives of Current Research International, 2025)
Indian agriculture faces various challenges such as small and fragmented landholdings, water scarcity, soil degradation, low productivity, market access issues, post-harvest losses, and vulnerability to climate. Late blight caused by Phytophthora infestans poses a significant threat to tomato productivity, leading to drastic reductions in plant growth and yield. Many bio-control agents, such as certain microbial species and beneficial fungi, can enhance soil health by improving nutrient cycling, suppressing soil-borne diseases, and promoting plant growth. The present study evaluates the efficacy of various aqueous plant extract formulations T1 to T5 prepared from Carica papaya, Syzygium cumini, and Lantana camara in mitigating the morphological and physiological impacts of the pathogen under in conditions. The diseased control exhibited severe stunting, leaf curling, and reduced reproductive traits. Among the treatments, T3 consistently demonstrated superior recovery in both vegetative and reproductive parameters. T3-treated plants recorded a shoot length of 69.4 cm, tap root length of 9.7 cm, and 99 lateral roots—values closely approximating the healthy control. Significant improvements were observed in leaf surface area (31.92 cm²), internodal length (13.3 cm), and stomatal index (13.34), indicating restored physiological function. T3 also outperformed other treatments in reproductive metrics, registering 90 flowers/plant, 17 fruits/plant, 57 seeds/fruit, and a fruit weight of 106.35 g, which is markedly higher than the diseased control (6.72 g). Additionally, near-normal leaf morphology and enhanced fruit pulp thickness (0.6 cm) confirmed visible plant recovery. While T4 and T5 also showed moderate improvements, their performance was inferior to T3 across key indicators. The results underscore the potential of specific plant-based formulations in suppressing P. infestans and enhancing tomato plant resilience. In conclusion, the study highlights T3 as the most effective treatment for promoting recovery from late blight, offering a promising, eco-friendly alternative to conventional fungicides in integrated disease management strategies. This study therefore provides strong evidence supporting the use of plant-based foliar sprays in integrated disease management strategies, particularly in smallholder and organic farming systems, contributing to safer crop protection and enhanced food security.